A case of SARS‐CoV‐2‐associated arthritis with detection of viral RNA in synovial fluid. Issue 4 (26th July 2021) - Kuschner, Zachary; Ortega, Alexandra; Mukherji, Pinaki
Abstract: Severe acute respiratory distress syndrome‐coronavirus‐2 (SARS‐CoV‐2) provokes symptoms ranging from mild viral illness to a systemic inflammatory syndrome with multi‐organ failure and has been associated with cases of arthritis. We report a clinical case of SARS‐CoV‐2 associated arthritis in which analysis of synovial fluid detected SARS‐CoV‐2 ribonucleic acid.